2002
DOI: 10.1002/jbm.10333
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the tensile properties of polyvinyl alcohol hydrogel for the construction of a bioprosthetic heart valve stent

Abstract: Although bioprosthetic heart valves offer the benefits of a natural opening and closing, better hemodynamics, and avoidance of life-long anticoagulant therapy, they nevertheless tend to fail in 10-15 years from tears and calcification. Several authors, including the present ones, have identified the rigid stent as a factor contributing to these failures. The ultimate solution is an artificial heart valve that has mechanical properties that allow it to move in conformity with the aortic root during the cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
166
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(183 citation statements)
references
References 24 publications
8
166
0
1
Order By: Relevance
“…15,17,18 SANS Data Analysis. 2-D patterns of absolute scattering intensity were obtained for each sample and each q range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,18 SANS Data Analysis. 2-D patterns of absolute scattering intensity were obtained for each sample and each q range.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] The mechanical properties of PVA are similar to the characteristics of soft tissues, displaying an exponential stress-strain curve that can be altered by changing several physical cross-linking parameters. 15, 16 Wan et al 15 reported PVA samples that matched the circumferential direction in porcine aortic root up to 35% strain. Millon et al 17 reported a PVA-bacterial cellulose nanocomposite that was able to closely match the mechanical properties of porcine aorta in either circumferential or axial directions up to 70% strain as well as a nanocomposite with high composition of both components which fell within the range displayed by heart valve tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Such factors may influence the motion of the biomodeling when there is pulsatile flow in its lumen, as may the mechanical interaction between the biomodeling and the interventional devices during the training of endovascular intervention. Methods of representing these factors of a blood vessel with PVA-H have been reported by Wan et al (23) and Millon et al (24), (25) . Wan et al first indicated that PVA-H can represent the nonlinearity of a blood vessel in a tensile test by performing freeze-thaw cycles, which is a method in which PVA gel is repeatedly frozen and thawed.…”
Section: Discussionmentioning
confidence: 99%
“…The strain applied to the uniaxial S2-shaped PVA-C + BC samples was optically measured using the extensometer on the Zwick tensile testing machine by tracking the two reflective points to the sample. The system was fitted with a 50 N load cell and a comprehensive uniaxial test protocol was developed which incorporated methodology utilized by Wan et al (2002), Dineley et al (2006) and Fromageau et al (2007) to mechanically characterize the PVA-C samples. A feed rate of 5 mm min -1 , which was common to all three studies, was selected and the samples prepared from each freeze-thaw cycle were subjected to 6 stress strain cycles to a maximum displacement of 80 % of the gauge length.…”
Section: Measurement Of Viscoelastic Properties Of Pva-c + Bc (Batch mentioning
confidence: 99%